Synergistic Activity of Clofazimine and Clarithromycin in an Aerosol Mouse Model of Mycobacterium avium Infection - Lanoix, Jean-Philippe; Joseph, Cédric; Peltier, François; Castelain, Sandrine; Andréjak, Claire (Antimicrobial agents and chemotherapy, 2020)
Infections with nontuberculous mycobacteria (NTM) have a poor prognosis in patients with underlying respiratory diseases. Clofazimine (CFZ) showed both experimental and clinical promising results against clinically relevant NTM. However, there are no data on CFZ in combination with the current recommended treatment; therefore, we aimed to study its activity in an aerosol mouse model of In an aerosol infection BALB/c mouse model using strain Chester, we treated 58 mice with four combinations of rifampin (RIF) at 10 mg/kg, CFZ at 25 mg/kg, and clarithromycin (CLR) and ethambutol (EMB) at 100 mg/kg. Treatment efficacy was assessed on the basis of lung CFU counts after 2 (M2) and 4 (M4) months of treatment. At M2, CLR-RIF-EMB was slightly but significantly more efficient than CFZ-RIF-EMB (3.02 ± 0.12 versus 3.55 ± 0.28, respectively, < 0.01), whereas CLR-CFZ-EMB and CLR-CFZ-RIF-EMB dramatically decreased lung CFU counts by 4.32 and 4.47 log , respectively, compared to untreated group. At M4, CLR-RIF-EMB was significantly more efficient than CFZ-RIF-EMB (2 ± 0.53 versus 2.66 ± 0.22, respectively, = 0.01). The addition of CLZ to CLR dramatically decreased the lung CFU count, with CFU counts 5.41 and 5.79 log lower in the CLR-CFZ-EMB and CLR-CFZ-RIF-EMB groups, respectively, than in the untreated group. The addition of CFZ to CLR seems to improve the efficacy of CLR as early as M2 and was confirmed at M4. CFZ, in addition to RIF and EMB, on the other hand, is less effective than CLR-RIF-EMB. These results need to be confirmed by similar studies along with CFZ potential for shortening treatment.